2018
DOI: 10.1371/journal.pone.0205869
|View full text |Cite
|
Sign up to set email alerts
|

The effects of electrical stimulation of the peripheral vestibular system on neurochemical release in the rat striatum

Abstract: For over a century, it has been speculated that the vestibular system transmits information about self-motion to the striatum. There have been inconsistent reports of such a connection, and interest in the subject has been increased by the experimental use of galvanic vestibular stimulation in the treatment of Parkinson’s Disease patients. Nonetheless, there are few data available on the effects of vestibular stimulation on neurochemical changes in the striatum. We used in vivo microdialysis to analyse changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 58 publications
(83 reference statements)
1
10
0
Order By: Relevance
“…Stiles et al (59) have also recently reported that c-Fos expression, as a marker of cellular activation, and the firing rate of a circumscribed number of single striatal neurons, can be altered by electrical stimulation of the vestibular labyrinth in the anesthetized rat (see Figures 2–4). In related studies, they also demonstrated that such electrical stimulation can modulate the release of serine, threonine and taurine, as well altering DA metabolism (60).…”
Section: Neural Circuitry Underlying Effects Of Vestibular Stimulatiomentioning
confidence: 98%
See 2 more Smart Citations
“…Stiles et al (59) have also recently reported that c-Fos expression, as a marker of cellular activation, and the firing rate of a circumscribed number of single striatal neurons, can be altered by electrical stimulation of the vestibular labyrinth in the anesthetized rat (see Figures 2–4). In related studies, they also demonstrated that such electrical stimulation can modulate the release of serine, threonine and taurine, as well altering DA metabolism (60).…”
Section: Neural Circuitry Underlying Effects Of Vestibular Stimulatiomentioning
confidence: 98%
“…It does appear that field potential changes are easier to record in the striatum in response to electrical stimulation of the peripheral vestibular system, at least in anesthetized rats (46, 59). Nonetheless, taken together with neurotracer studies [e.g., (61)] and other evidence from microdialysis studies (60), there is evidence for connections between the vestibular nucleus complex and cerebellum and the striatum. Certainly, more studies are needed to elucidate these connections, using selective electrical stimulation of the vestibular labyrinth and both neuronal recording and neurotransmitter microdialysis in the striatum (100, 101).…”
Section: Conclusion and Future Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the largest inputs to the striatum are from the cortex, recent studies have elucidated the subcortical pathways critical for interpreting and responding to environmental stimuli ( 66 , 67 ). Electrophysiological studies in animal models and neuroimaging studies in humans have shown that vestibular stimulation activates the head of the caudate nucleus and putamen ( 16 19 , 62 , 68 , 69 ), likely through the parafascicular thalamic nucleus (PFN) ( 64 , 70 ). In addition, it has been recently proposed that the striatal tail may play a role as a multisensory integration center ( 71 ), and thus it is possible that there are vestibular inputs to this region as well.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of time-varying CVS, transcranial Doppler sonography of the basilar artery shows a significant increase in cerebral blood flow velocity that is consistent with modulation of brainstem centers [26]. In the case of GVS, there are changes in EEG power spectra and P300 morphology [19,[27][28][29] and in rats, there are reports of hippocampal cell proliferation [30] striatal reductions in c-FOS expression, and serine and threonine release [31,32].…”
Section: Article Highlightsmentioning
confidence: 99%